EMPLOYEE PARTICIPATION RIGHTS NEGOTIATION IN COMPANIES RESULTING FROM A CROSS-BORDER MERGER - Felicia BEJAN (Challenges of the Knowledge Society, 2018)
The cross-border merger may have major consequences on the employee rights of the companies undergoing this process. The employees find themselves before two great uncertainties. The first one regards the continuity of the labor contract under the rights acquired before the merger, with respect to which the European legislator adopted Directive 2001/23/CE on the approximation of the laws of the Member States relating to the safeguarding of employees' rights in the event of transfers of undertakings, businesses or parts of undertakings or businesses. The second one refers to maintaining the employee participation right to the administration and supervision of companies, where they exist, in the company resulting from the cross-border fusion process, right protected at European level through article no. 16 of the Directive 2005/56/EC on crossborder mergers of limited liability companies, completed with Regulation(EC) 2157/2001 in the Statute for a European company and with Directive 2001/86/EC supplementing the Statute for a European company with regard to the involvement of employee. The employee participation rights in resulting companies from a cross-border merger and the way they are negotiated are aspects of great importance in influencing the make-decision process regarding to operate or not such reorganization. The paper aims to achieve to an analyses of the legal framework provided by the European norms on the negotiation of participation rights of employees in the event of a cross-border merger, emphasizes the aspects with regard to which the regulation in the domain requires to be modified and proposes the lege ferenda amendments.